(untitled) - 2002-; Pine, Chris; 1980-; Mbatha-Raw, Gugu; 1983-; Galifianakis, Zach; Péna, Michael; 1976-; Young, Bellamy; Miller, Levi; Oyelowo, David; Djawadi, Ramin; et al. (Burbank, CA, 2018)
Following the discovery of a new form of space travel as well as Megs fathers disappearance, she, her brother, and her friend must join three magical beings (Mrs. Whatsit, Mrs. Who, and Mrs. Which) to travel across the universe to rescue him from a terrible evil.
Keywords: Time travel; Juvenile drama; Fathers and daughters; Juvenile drama; Juvenile drama; Families; Juvenile drama; Brothers and sisters; Juvenile drama; Space and time; Action and adventure films; Video recordings for the hearing impaired; Feature films; Childrens films